Association Between Soil Patterns and Mortality with Distinct Types of Cancers and CVD Across the USA - Bingjie Qu; Qiaochu Xu; Linxi Yuan; Ying Chen (Life)
Mineral elements are essential for human health. Our previous study identified distinct clusters of health-related mineral elements in surface soil among different regions and demonstrated an association between these clusters and health profiles in the USA. The present study further explores the relationship between these mineral clusters and mortality from detailed specific types of cancers and cardiovascular diseases by using county-level data from 3080 counties across the USA. Utilizing multivariate regression models with adjustment for socio-demographic and geographical factors, our analysis of county-level data revealed that residents in the regions of ‘infertile’ cluster have higher mortality rates for most types of cancers (18/29) and cardiovascular conditions (4/10) compared with people who live elsewhere. Notably, this relationship is pronounced for several specific leading causes of death such as tracheal, bronchus, lung cancer (regression coefficient (99.5% CIs), 6.29 (4.46, 8.13)), prostate cancer (1.06 (0.53, 1.6)), cerebrovascular disease (3.15 (1.74, 4.55)), and hypertensive heart disease (1.23 (0.23, 2.23)). Our findings highlight the critical role of soil minerals in human health and underscore the need for integrating geochemical data in public health strategies and environmental management policies.